2022
DOI: 10.1186/s13019-022-01899-3
|View full text |Cite
|
Sign up to set email alerts
|

Early results of totally endoscopic robotic aortic valve replacement: analysis of 4 cases

Abstract: Objective To evaluate the role of totally endoscopic robotic aortic valve replacement in cardiac surgery. Methods Four cases of totally robotic aortic valve replacement (AVR) were conducted from December 2016 to July 2018. All operations were completed with the Da Vinci robot Si™ system (intuitive Surgical, Inc. Sunnyvale, C.A, USA). Patients were male, with a mean age of 42.8 ± 6.2 years (range 32–49). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, Sun points to the lack of a proper hook to expose the valve, difficulties in suturing the aortic annulus and long knotting time, as well as difficult cooperation with the assistant. However, as he himself notes, this may be due to the team’s limited experience [ 59 ]. In reports on RAVR, the achieved aortic clamping time and CPB time were much longer than in classic surgical aortic valve replacement procedures.…”
Section: Cardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Sun points to the lack of a proper hook to expose the valve, difficulties in suturing the aortic annulus and long knotting time, as well as difficult cooperation with the assistant. However, as he himself notes, this may be due to the team’s limited experience [ 59 ]. In reports on RAVR, the achieved aortic clamping time and CPB time were much longer than in classic surgical aortic valve replacement procedures.…”
Section: Cardiac Surgerymentioning
confidence: 99%
“…In reports on RAVR, the achieved aortic clamping time and CPB time were much longer than in classic surgical aortic valve replacement procedures. This has a direct impact on the duration of cardiac ischaemia and the procedure [ 57 , 58 , 59 ]. Therefore, RAVR is not a good choice for patients with contractility disorders of the heart, low left ventricular ejection fraction, and high operative risk.…”
Section: Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Research in robotic valve replacement started with the use of the Da Vinci surgical system in 2005 [8] and continued in 2010 with the complete excision of diseased native aortic valve leaflets and the accurate placement of a Sorin Perceval artificial valve [9]. Although robotic cardiac surgery has demonstrated several benefits, such as smaller incisions, motion scaling, and enhanced visualization [10], [11], [12], [13], the introduction of the Da Vinci robot into cardiac surgery has been slow, mainly because its grasping solutions are not designed for holding and manipulating the artificial valve [14], [15]. To overcome the abovementioned limitations, dedicated robotic systems were introduced for aortic heart valve surgery, albeit with rigid sheath and limited actuation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Research on body image has also been conducted in other countries, examining diverse patient populations, including those receiving hemodialysis, undergoing renal transplantation (Rezai et al, 2009 ), dealing with heart failure (Goudarzian et al, 2016 ), and undergoing heart surgery (Lyigun et al, 2017 ). Among patients who have undergone coronary artery bypass grafting (CABG), previous studies have shown that surgical scars on the chest can result in a loss of positive body image if the patients are unable to accept these physical changes (Sun et al, 2022 ). Iyigun et al ( 2017 ) reported that 84% of post-CABG patients experienced a negative perception of body image or a decrease in positive body image due to the presence of surgical scars.…”
Section: Introductionmentioning
confidence: 99%